Negative effects of delayed retirement: Employment protection of older workers and firm value - Chino, Atsushi (Journal of Corporate Finance, 2025)
Does protecting the employment of older workers affect firm value? We investigate this question by leveraging a labor-market reform in Japan that mandated firms to retain older employees beyond the statutory retirement age if those employees wished to continue working. An event study analysis reveals that firms with higher exposure to the reform experienced lower short-run abnormal stock returns around the announcement date. Long-run difference-in-differences estimates provide supporting evidence. In affected firms, average wages rose following the reform, but worker productivity remained unchanged. We also find that the number of patent applications declined in the affected firms. These findings suggest that mandatory employment protection for older workers—when not accompanied by productivity gains—can negatively impact firm value.